Deciphering Object-Oriented Programming with C++ : A Practical, in-Depth Guide to Implementing Object-oriented Design Principles to Create Robust Code. - Kirk, Dorothy R. (Packt Publishing, Limited, 2022)
Embrace object-oriented programming and explore language complexities, design patterns, and smart programming techniques using this hands-on guide with C++ 20 compliant examples. Even though object-oriented software design enables more easily maintainable code, companies choose C++ as an OO language for its speed. Object-oriented programming in C++ is not automatic - it is crucial to understand OO concepts and how they map to both C++ language features and OOP techniques. Distinguishing your code by utilizing well-tested, creative solutions, which can be found in popular design patterns, is crucial in today's marketplace. This book will help you to harness OOP in C++ to write better code. Starting with the essential C++ features, which serve as building blocks for the key chapters, this book focuses on explaining fundamental object-oriented concepts and shows you how to implement them in C++. With the help of practical code examples and diagrams, you'll learn how and why things work. The book's coverage furthers your C++ repertoire by including templates, exceptions, operator overloading, STL, and OO component testing. You'll discover popular design patterns with in-depth examples and understand how to use them as effective programming solutions to solve recurring OOP problems. By the end of this book, you'll be able to employ essential and advanced OOP concepts to create enduring and robust software.